Electrophysiological evaluation of Cystic Fibrosis Conductance Transmembrane Regulator (CFTR) expression in human monocytes - Ettorre, Michele; Verzè, Genny; Caldrer, Sara; Johansson, Jan; Calcaterra, Elisa; Assael, Baroukh Maurice; Melotti, Paola; Sorio, Claudio; Buffelli, Mario (Biochimica et biophysica acta, 2014)
Cystic fibrosis is caused by mutations of CFTR gene, a protein kinase A-activated anion channel, and is associated to a persistent and excessive chronic lung inflammation, suggesting functional alterations of immune cells. Leukocytes express detectable levels of CFTR but the molecule has not been fully characterized in these cells. Freshly isolated monocytes from healthy individuals and CF patients were assessed by protein expression, single cell electrophysiological and membrane depolarization assays. We recorded chloride currents by patch clamp in healthy monocytes, after the administration of a CFTR stimulus. Currents were sensitive to a specific blocker of the CFTR channel, CFTRinh-172 and were absent in CF monocytes. Next, we evaluated the effects of ex vivo exposure of monocytes from cystic fibrosis patients carrying the F508del mutation to a chemical corrector, Vertex-325. We found an increase in CFTR expression by confocal microscopy and a recovery of CFTR function by both patch clamp and single cell fluorescence analysis. We confirm the expression of functional CFTR in human monocytes and demonstrate that blood monocytes can represent an adequate source of primary cells to assess new therapies and define diagnosis of CF. Tests to evaluate CFTR functional abnormalities in CF disease might greatly benefit from the availability of a convenient source of primary cells. This electrophysiological study promotes the use of monocytes as a minimally invasive tool to study and monitor CFTR function in individual patients. •Human non CF monocytes express a functional CFTR.•F508del CF monocytes recover CFTR function after ex vivo exposure to Vertex-325.•Monocytes as a possible support for diagnosis and drug development for CF